Bacterial keratitis: identifying the areas of clinical uncertainty. (July 2022) - Tuft, Stephen; Somerville, Tobi F.; Li, Ji-Peng Olivia; Neal, Timothy; De, Surjo; Horsburgh, Malcolm J.; Fothergill, Joanne L.; Foulkes, Daniel; Kaye, Stephen
Abstract: Bacterial keratitis is a common corneal infection that is treated with topical antimicrobials. By the time of presentation there may already be severe visual loss from corneal ulceration and opacity, which may persist despite treatment. There are significant differences in the associated risk factors and the bacterial isolates between high income and low- or middle-income countries, so that general management guidelines may not be appropriate. Although the diagnosis of bacterial keratitis may seem intuitive there are multiple uncertainties about the criteria that are used, which impacts the interpretation of investigations and recruitment to clinical studies. Importantly, the concept that bacterial keratitis can only be confirmed by culture ignores the approximately 50% of cases clinically consistent with bacterial keratitis in which investigations are negative. The aetiology of these culture-negative cases is unknown. Currently, the estimation of bacterial susceptibility to antimicrobials is based on data from systemic administration and achievable serum or tissue concentrations, rather than relevant corneal concentrations and biological activity in the cornea. The provision to the clinician of minimum inhibitory concentrations of the antimicrobials for the isolated bacteria would be an important step forward. An increase in the prevalence of antimicrobial resistance is a concern, but the effect this has on disease outcomes is yet unclear. Virulence factors are not routinely assessed although they may affect the pathogenicity of bacteria within species and affect outcomes. New technologies have been developed to detect and kill bacteria, and their application to bacterial keratitis is discussed. In this review we present the multiple areas of clinical uncertainty that hamper research and the clinical management of bacterial keratitis, and we address some of the assumptions and dogma that have become established in the literature. Highlights: There is no agreement on the criteria that should define bacterial keratitis. The role of investigation is unclear, particularly how this affects outcomes. A diagnostic rule establishes how to interpret isolates whether identified from culture or metagenomics. New technologies for investigation should enable personalisation of treatment. Non-antibiotic therapies are being introduced encompassing phage and anti-virulence compounds.